The formation of the prisoner-theologian Dietrich Bonhoeffer: a close reading of Letters and papers from prison, from April 5,1943 to July 20, 1944 - Adams, Daniel Clayton (Department of Religious Studies, 2015)
This thesis seeks to take Dietrich Bonhoeffer’s prison experience seriously as a spiritually and theologically formative journey through liminal displacement. Using the anthropological theory of liminality as a lens for analysis, it offers a close reading of Bonhoeffer’s prison writings, examining the porous nature of the sociocultural and metaphorical boundaries of the prison space as expressed in notes, letters, essays, prayers, poetry, and theological letters. In doing so, the thesis suggests that Bonhoeffer’s dramatic transition into the prison space results in an “inbetween- ness” (Palmer et al. 2009) that suspends the prisoner “betwixt and between” (Turner 1967) light and dark, inside and outside, above and below, sacred and profane space, dislocation and located-ness, suffering and hope, life and death. Chronologically examining distinct phases of liminality – separation, transition, anticipation – the study shows a cumulatively transformative movement in which the prisoner is drawn ever more deeply into the reality of his own life, and an ever increasing relationality with others, with God, and with the suffering of those who inhabit the view from below. It is observed that by taking an active role in navigating liminality, Bonhoeffer encounters multiple turning points at the heart of betwixt space, which break up “default modes of perception,” (Wannenwetsch 2012) transforming the prison cell into a privileged place of insight that ultimately catalyses a transformative new vision of reality and the Christian life. Within liminality the borderlines and boundaries of the prison space remain just porous enough to create the possibility for alternative ways of viewing reality. Through theological, poetic, and polyphonic anticipation, Bonhoeffer risks imaginative resolve by reframing liminality as a Gethsemane-like displacement, stations on the way to freedom, and participation in the polyphonic nature of life. In it is concluded that Bonhoeffer’s prison experience represents a uniquely formative space in which he was drawn into participation in the life, sufferings, and death of Jesus Christ.